Synthesis Characterization and Analytical Applications of New Chelating Resin of Formaldehyde-condensed Phenolic Schiff base. - Abas Omran, khalida; Omran Lafta, Shayma (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
A new chelating phenolic Schiff base containing phthalate imide pendant group resin was synthesized by three steps. The first step includes synthesis of 2-(4-aminobiphenyl-4-ylcarbamoyl) benzoic acid (1), Via reaction of pthalic anhydride with benzidine. In the second lines, the compound that we obtained in the first step was reacted with o-hydroxybenzaldehyde to obtain phenolic Schiff base 2-(4’-(2-hydroxybenzylideneamino) bephenyl-4-yl carbamoyl) benzoic acid (2) The third step includes prepared resin during intensification Schiff base derived with formaldehyde inan alkaline middle. Thepthale amice acid, Schiff base and resin were characterized by various instrumental techniques like FT-IR, 1HNMR ,13CNMR and elemental analysis, thermal behavior of the polymer was investigated by DSC and TGA.SEM analysis of polymer shows the amorphous structure of polymer. The chelating behaviors was examined against Ni (á´¨), Cd (á´¨), Cr(Ñˆ)and Pb(á´¨). using patch method in different conditions like treatment time and pH at room temperature. The resin shows a good loading capacity